Relationship between school principal leadership style and teachers' job satisfaction in a private school / Erni Irdayanti Ahmad - Ahmad, Erni Irdayanti (2014)
Leadership is a process where a leader attempts to influence the behavior of subordinates to achieve the organizational goals. Organizational success and effectiveness lies in the hands of effective leaders displaying effective leadership styles. By adopting the appropriate leadership styles, leaders can affect employee job satisfaction. Therefore this case study aimed to investigate the relationship between school principal leadership style and teachers' job satisfaction level. This was a descriptive correlation study using a mixed-methods research design. The study was conducted in a randomly selected private school located in the Klang valley and involved the total population of 62 teachers and the school principal. Data was collected through the use of a questionnaire and semi structured interviews with 6 randomly selected teachers from the total population of 62 teachers. The findings of the study revealed that the school principal fairly often practiced the transformational leadership style and sometimes practiced the transactional leadership style. The results also showed that transformational leadership style of the principal had a weak and significant relationship with job satisfaction. Hence the teachers expressed an overall moderate level of job satisfaction working in the school highlighting that they were most satisfied with the nature of their work and their co-workers. Besides that, the principal also pointed out that the main challenges that she faced in maintaining teachers' job satisfaction level was related to issues surrounding pay, rewards, working conditions, supervision and communication. The findings of this study imply that transformational and transactional leadership style is deemed suitable for not only maintaining teacher job satisfaction levels but also school effectiveness. Henceforth, it is pertinent that authorities in private schools also look into leadership training initiatives for private school principals. Such a move would enhance teachers' job satisfaction levels as teachers are often viewed as agents of change contributing to school success and school effectiveness.